Minutes (extract) : The International Brigade
034-0169-001 Extract from Minutes of National Council of Labour 23rd November 1937 30. THE INTERNATIONAL BRIGADE: Sir Walter Citrine reported an appeal he had received for recognition and assistance on behalf of the dependents and wounded members of the International Brigade. Sir Walter indicated that at the moment contribution to the International Solidarity Fund (see Appendix I) had ceased largely owing to the competing appeals, and it was RESOLVED: "That in the circumstances no action could be taken on the lines proposed' 292/946/34/169